Saving behavior of final year students in the Early Childhood Education Program, Faculty of Education, Ramkhamhaeng University - Teravecharoenchai, Thitinun; Thongeiam, Bongkoch; Rangsiyanon, Kwanfah; Ponerut, Tuschapone; Suthongsa, Supaluck (Journal for Developing the Social and Community, 2026)
Background and Aims: The high volatility in social, political, and trade stability, along with natural disasters, pandemics, pollution, and unforeseen events both domestically and internationally, currently impacts the Thai economy and the daily lives of its citizens in various dimensions. Teachers play a crucial role as role models and transmitters of knowledge, leading to student learning. Therefore, developing financial literacy according to professional standards, with a development framework starting from the individual level and progressing to professional transmission within the current Thai education context, is essential. This research aims to study the saving behavior and factors related to saving behavior among final-year students in Early Childhood Education, Faculty of Education, Ramkhamhaeng University. Methodology: This quantitative research used questionnaires to survey a sample of 82 final-year undergraduate students in Early Childhood Education at Ramkhamhaeng University’s Faculty of Education in academic year 2025 who were saving money. General information and saving behavior were analyzed using frequency and percentage calculations. The relationship between personal factors, financial management, saving motivation, attitude towards saving, and financial literacy was analyzed using the Chi-Square Test to determine the relationship between the students’ saving behavior. Results: All personal factors are related to saving behavior in all aspects. Financial management is related to saving behavior in terms of the source of savings. Motivation to save is related to saving behavior in two aspects: the duration of saving and the frequency of saving. Attitudes towards saving are related to saving behavior in two aspects: the frequency of saving and the amount of saving. Financial literacy is related to saving behavior in terms of the amount of savings. All factors are statistically significantly related to saving behavior. Conclusion: Personal factors, financial management, motivation to save, attitude towards saving, and financial literacy are significantly related to the saving behavior of final-year students in Early Childhood Education, Faculty of Education, Ramkhamhaeng University.